Evaluasi Uprating Transformator Distribusi 20 KV pada Penyulang Kelinci di PT. PLN (Persero) ULP Rumbai - Usaha Situmeang; Pangestu, Aji; Monice, Monice (SURYA TEKNIKA, 2024)
The need for electrical energy affects the loading of the transformer which can result in overloading of more than 80%. PLN Standard No. 50 of 1997 states that a transformer is said to be overloaded if the load is more than 80%. This research aims to determine the effect of loading on transformer efficiency and voltage drop on distribution transformers. For loading on transformers before uprating, the results were 92.143%. The voltage drop percentage value obtained for each phase R, S, T is 11.121%, voltage drop percentage on the R phase, 10.973% voltage drop percentage on the S phase, 10.167% voltage drop percentage on the T phase. Uprating was carried out on the transformer to reduce overloading. After the uprating was carried out, the loading results were 55.568 % , which was in accordance with the permitted loading standards. The voltage drop percentage value obtained for each phase R, S, T is 10.973%, voltage drop percentage on the R phase, 10.524 % voltage drop percentage on the S phase, 9.637 % voltage drop percentage on the T phase.